Improving Early Discharge Using a Team-Based Structure for Discharge Multidisciplinary Rounds. Issue 2 (March 2019) - Patel, Hemali; Yirdaw, Essey; Yu, Amy; Slater, Lisa; Perica, Katharine; Pierce, Read G.; Amaro, Connie; Jones, Christine D.
Abstract : Purpose of Study: Miscommunications during the complex process of discharging patients from acute care facilities can lead to adverse events, patient dissatisfaction, and delays in discharge. Brief multidisciplinary discharge rounds (MDRs) can increase communication between stakeholders and shorten a patient's length of stay (LOS). At our tertiary academic medical center, case managers (CMs) have historically been assigned patients by physical unit location rather than by provider teams caring for patients. As a result, medicine teams often interact with several unit-based CMs due to lack of geographically cohorted patients, leading to inefficiency and fragmentation in discharge planning communication. Our aim was to implement and evaluate the impact of multidisciplinary, team-based discharge planning rounds (MDR) for general medicine patients. Primary Practice Setting: A tertiary academic medical center. Methodology and Sample: Using the model for continuous improvement, we implemented and optimized MDR on 2 of 4 internal medicine resident ward teams that care for general internal medicine patients, including creation of a multidisciplinary team, improving physician continuity. Results: During the pilot, 1, 584 patients were discharged from all medicine teams—825 from pilot teams and 759 from control teams. The proportion of patients with discharge before noon (DBN) orders was 41.2% on pilot versus 29.6% on control teams. Length of stay was 92.2 hr versus 97.2 hr, and 30-day readmission rate was 16.0% versus 18.3% for the pilot versus control teams, respectively. After the pilot concluded, we continued to have resident continuity on pilot teams but returned to the unit-based CM model. During this time, the proportion of DBN orders and LOS were similar between the pilot and control teams (29.0% vs. 24.3% and 95.8 hr vs. 96.6 hr, respectively). The 30-day readmission rate was 12.6% compared with 18.9% for the pilot versus control teams. Implications for Case Management Practice: Our team-based MDR pilot improved interdisciplinary relationships and communication and resulted in shorter LOS, earlier discharge times, and lower 30-day readmissions.